Comparative utility of dual spectral computed tomography and functional magnetic resonance imaging in the preoperative evaluation of unstable fractures of the craniocervical complex: a systematic review of diagnostic accuracy and neurosurgical outcomes - Jiménez-Sánchez, Jesús; Pillajo, Lidia Leonor Chanchay; Amezcua, Noe Zamora; Chávez, Alfredo Carlos; Espinosa, Juan José Torres; Vivas, Juan Carlos Arce (International Journal of Research in Orthopaedics, 2025)
This systematic review critically appraises the sensitivity and clinical applicability of dual-energy computed tomography (DECT) compared with functional magnetic resonance imaging (fMRI) in evaluating unstable fractures involving the craniocervical complex and vertebral muscles. Nine studies were included, comprising retrospective cohorts, prospective diagnostic trials, and meta-analyses, with sample sizes ranging from 8 to 515 patients and heterogeneous fracture types. DECT demonstrated strong diagnostic performance in several contexts. For bone marrow edema (BME), DECT achieved 89% sensitivity, 98% specificity, and an AUC of 0.96 (p<0.001). In intervertebral disc injuries, sensitivity and specificity were 0.85 and 0.75, with significant attenuation differences (p<0.001). For pelvic fractures, DECT reached 89.5% sensitivity and 84.6% specificity, with moderate inter-rater reliability (kappa=0.516). Optimization with electron density imaging improved hematoma detection, raising sensitivity and specificity above 80% (kappa=0.82; p=0.04). Meta-analytic results confirmed overall sensitivity, specificity, and accuracy of 86.2%, 91.2%, and 89.3%, respectively. Nonetheless, MRI clearly outperformed CT in detecting ligamentous injuries and occult trauma, with a negative predictive value of 100% for cervical instability. Limitations of the current evidence include small samples, retrospective designs, interobserver variability, and incomplete subgroup analyses. Despite these, DECT remains a promising adjunct or alternative when MRI access is limited, particularly for BME and fracture line imaging. Future multicenter studies are needed to standardize protocols and strengthen generalizability.